1999
DOI: 10.1128/iai.67.3.1267-1276.1999
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activities and Epitope Specificity of Human and Murine Antibodies against the Class 4 Outer Membrane Protein (Rmp) of Neisseria meningitidis

Abstract: Antibodies against the class 4 outer membrane protein (OMP) fromNeisseria meningitidis have been purified from sera from vaccinees immunized with the Norwegian meningococcal group B outer membrane vesicle vaccine. The human sera and purified antibodies reacted strongly with the class 4 OMP in immunoblots, whereas experiments with whole bacteria showed only weak reactions, indicating that the antibodies mainly reacted with parts of the class 4 molecule that were not exposed. The purified human anti-class 4 OMP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…The other major antigen common to all N. meningitidis and N. lactamica strains, also recognised by all sera, has an apparent molecular mass of approximately 32 kDa and is not regulated by iron levels. This antigen could be the meningococcal class 4 protein, exhaustively studied because it is antigenically invariant and able to induce antibodies that block the bactericidal activity of other antibodies, although this activity has recently been questioned [31]. The class 4 protein has a molecular mass between 32 and 34 kDa, but it is not clear that the meningococcal class 4 proteins have antigenic cross-reactivity with N. lactamica strains [32].…”
Section: Discussionmentioning
confidence: 99%
“…The other major antigen common to all N. meningitidis and N. lactamica strains, also recognised by all sera, has an apparent molecular mass of approximately 32 kDa and is not regulated by iron levels. This antigen could be the meningococcal class 4 protein, exhaustively studied because it is antigenically invariant and able to induce antibodies that block the bactericidal activity of other antibodies, although this activity has recently been questioned [31]. The class 4 protein has a molecular mass between 32 and 34 kDa, but it is not clear that the meningococcal class 4 proteins have antigenic cross-reactivity with N. lactamica strains [32].…”
Section: Discussionmentioning
confidence: 99%
“…These include vaccines based on eliciting antibody to the group B capsule [22,23] or to non-capsular antigens. The non-capsular approaches include outer membrane vesicle (OMV) vaccines [24^27], speci¢c outer membrane proteins (OMPs) such as PorA [28^34], iron-regulated proteins [35^37], class 4 (Rmp) proteins [38], Opc [39], Neisserial surface protein A [40,41] and detoxi¢ed lipopolysaccharide [42^46]. In this minireview, we summarize the status of some of the more promising and/or clinically advanced approaches for development of a meningococcal B vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…It has been described that mouse MoAb to RmpM can block bactericidal killing by anti-PorA MoAb [19]. Nevertheless, an elegant study by Rosenqvist et al [20] showed no blocking effect on bactericidal activity of MoAb anti-RmpM or immunoglobulin (Ig) anti-RmpM purified from serum of vaccinees. Of note, the human Ig anti-RmpM preparations were obtained from sera collected after two doses of the Norwegian Men B vaccine.…”
Section: Discussionmentioning
confidence: 99%